ALGORITMA PRIM YANG DIMODIFIKASI PADA MASALAH POHON PEMBANGUN MINIMUM FUZZY - Puteri, Ilma; Syafwan, Mahdhivan; Nazra, Admi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
This study aims to find the Minimum Spanning Tree (MST) on graphs with uncertain edge weights, which are modeled using triangular fuzzy numbers. To compare and sum the edge weights in determining the fuzzy MST, the layered average integration method is used. In graphs with crisp edge weights (real numbers), the MST problem can be solved using Prim's algorithm. This research develops and introduces a fuzzy version of Prim's algorithm to address the fuzzy MST problem on graphs with fuzzy edge weights. Additionally, an application example is provided to demonstrate the performance of the modified Prim's algorithm in determining the fuzzy MST. The results of this study offer an effective approach to handling uncertainty in graph edge weights using fuzzy methods and can be applied to various network problems involving data uncertainty.